PENGARUH PEMBERIAN PAKAN ALAMI DAN PAKAN KOMERSIL TERHADAP PERTUMBUHAN DAN SURVIVAL RATE IKAN JALAI (Channa marulioides) - Nuhman; ivan rahmad, ivan rahmad septiawan; Trisyani, Ninis (Universitas Hang Tuah, 2022)
Jalai fish is a freshwater fish that lives in the tropics of India, Indonesia, and the United States. This fish is known as the